Potensi dan Peluang Pengembangan Usaha Perikanan Tangkap Di Pantura Jawa Tengah - Triarso, Imam (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
The research on capture fisheries resources in north coastal of Central Java were to anticipate amount produce and effort of capture fisheries. Usefulness from this research expected to earn as reference of management of small scale fisheries and consideration alternative which can be taken for local government of Central Java Province. Primary data were collected from local fishers, while secondary data were collected from district and Marine and Fishery Services Central Java Province. Data series of 2006 to 2009 were also analyzed by bioeconomic analysis with surplus production model. The result indicate that condition of capture fisheries resources in North Coastal of Central Java were overfishing, included its several regency/city adjacent areas. The effort in developing fish capture has reached its boredom circumstance so this situation needs better maintenance and control toward the capturing activities. The policy expected to minimize exploitation of fishery resources on coastal area, and the vessel can more further to off shore and oceanic area. The government as a policy maker on fisheries management for coastal fisheries must applicable precautionary approach by focusing on biology and economic aspects. Key words: fisheries product, bio-economic model, small scale fisheries management